Analisis Perputaran Persediaan terhadap Profitabilitas Perusahaan Farmasi di Bursa Efek Indonesia - Lilian Atarina; Poniman Poniman (Universitas Batanghari, 2022)
Inventory turnover serves to determine the company's inventory that is sold and replaced within a certain time. Inventory turnover measures how well a company markets its inventory and will be compared to a balanced industrial company. Low inventory turnover indicates weak sales while high inventory turnover indicates influential sales. This study aims to examine and evaluate the effect of inventory turnover (at cost) and inventory turnover (at market) on profitability (ROA) of pharmaceutical companies on the Indonesia Stock Exchange in 2017-2021. This research is a quantitative research. The participants in this study were all manufacturing companies in the food and beverage sub-sector listed on the Indonesia Stock Exchange for the period 2017-2021. The sample size of this research is 8 companies. The results of the study concluded that inventory turnover (at cost) had a positive and significant effect on profitability. However, inventory turnover (at market) has a negative and insignificant effect on profitability. Meanwhile, inventory turnover (at cost) and inventory turnover (at market) simultaneously have a positive and significant effect on profitability (ROA).